Desain Huruf Media Cetak Leaflet pada Peningkatan Pengetahuan Ibu-Ibu tentang Bertanam Jahe di Kota Kendari - Isnian, Sitti Nur; Isnan, Sitti Nur (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2018)
The design of letters on a leaflet medium is very strategic considering letters are the main ingredient in conveying messages. This study aims to determine the effective letter design applied in Kendari City. This research was conducted in the Anduonohu Sub-District of Poasia Subdistrict which was chosen purposively with consideration of 1) Anduonohu Village was the representative of the city center and suburbs so that the results of the research could be repressive in Kendari City; 2) The extension method that is applied is the use of leaflet media in promoting living pharmacies to increase the knowledge of mothers. The population of this study was all program recipients with a total of 28 people, all of whom were respondents. The twenty-eight people were divided into 4 groups of 7 people each, to conduct experiments. This study uses an experimental method with the One Group Pretest-Posttest model, with a time series. The results showed that the upright design with the 12-point size of the arial type was effectively applied to increase the knowledge of mothers about growing ginger in Kendari City.